(untitled) (Sport and Tourism Central European Journal, 2019)
Introduction: The way of spending time by people is significant for individual and social wellbeing. Disorders regarding proportion of time dedicated to various activities may result in definite detrimental consequences for physical as well as mental health. The aim of the study was to compare patterns of using time by students majoring in physical education taking into account their sex and level education – and to refer them to a sample of the national population of a similar age. Moreover, the authors decided to make an analysis aimed at finding differences between the real and the desirable time of the researched students’ various activities during 24 hours. Material and methods: The study involved 191 students majoring in physical education from the External Faculty of the University of Physical Education in Biała Podlaska studying in the 6th semester of bachelor studies and in the 2nd semester of master studies during the academic year 2016/2017. Their average age was 22.74 1.10. Their use of time was studied with an activity card, which was filled out by the researched every single day for a week. For the purpose of a comparative analysis there were obtained data about use of time in a national sample of persons at the age 20–24 published by the General Statistical Office in 2015. Results: The studying women and men constituted an almost homogenous group regarding time dedicated to particular activities during 24 hours. The level of education turned out to be a variable which significantly differentiated the researched regarding their time dedicated to: lectures, theoretical lessons, using means of transport, watching TV, surfing the Internet, social life and professional activity. The researched students, when compared with the national sample, dedicated much more time to – among others – participation in sport and recreation, educational activities, whereas they spend less time on professional activity and sleeping. Conclusions: Our findings point out that a comprehensive analysis of using time can help in diagnosing negative habits and contribute to working out practical guidelines being useful for planning activities and promoting health.